Preparation, Structural Characterization and Biological Activity Study of Selenium-Rich Polysaccharides from Cyclocarya paliurus - Yulan Dong; Zijue Wang; Qinghui Xia; Juan Chen; Quanwei Lv; Shaopeng Zhang; Shuiyuan Cheng; Xiaoling Chen; Xingxing Dong (Foods)
In this study, we extracted, separated, and purified polysaccharides from Se-enriched Cyclocarya paliurus (Se-CPP-1) and compared them with their non-Se-enriched counterparts (CPP-1) to investigate the impact of selenium on their structural and functional properties. Structural characterization by HPLC, GC-MS, and SEM revealed that Se-CPP-1 is an acidic heteropolysaccharide with a lower molecular weight (76.6 vs. 109.22 kDa), smaller particle size (418.22 vs. 536.96 nm), and higher negative zeta potential (−43.15 vs. −21.29 mV), indicating enhanced colloidal stability. SEM imaging further demonstrated a distinctive flaky morphology in Se-CPP-1. Functional assays showed that Se-CPP-1 significantly outperformed CPP-1 in scavenging free radicals (DPPH/ABTS), stimulating RAW264.7 macrophage proliferation (CCK-8 assay), enhancing phagocytic activity, and promoting NO secretion. These improvements were attributed to selenium-induced modifications in polysaccharide conformation and surface properties. Our findings highlight the potential of selenium fortification in developing high-efficacy C. paliurus polysaccharides for antioxidant and immunomodulatory applications.